The Correlation of Self-Confidence, Concentration, and Goal Setting with Routine Training Scores among Archery Athletes at BPPLOP Central Java - Richa Lintang Amtajawi; Heny Setyawati; Tommy Soenyoto (Universitas Negeri Semarang, 2026)
In sports, there are several contributing factors including physical, technical, and psychological aspects. Among these, psychological factors particularly an athlete’s mental abilities play a significant role in performance. This study aims to examine the relationship between self-confidence, concentration, and goal setting on routine training scores. This research employed a test survey with a correlational approach and a cross-sectional design, meaning data was collected at one point in time. The sample consisted of 15 athletes, selected using a total sampling technique. The instruments used to collect data included: (1) Self-Confidence Scale, (2) Grid Concentration Test (GCT), (3) Goal Setting Scale, and (4) Training Score records. The results showed a strong and positive correlation between self-confidence, concentration, and goal setting with routine training scores. Specifically, self-confidence had a significant correlation with training scores (Sig. 2-tailed = 0.004), concentration (Sig. 2-tailed = 0.000), and goal setting (Sig. 2-tailed = 0.025). Furthermore, the combined influence of self-confidence, concentration, and goal setting on training scores was also significant, with a Sig. F Change value of 0.000 and an R square (R²) of 0.852. This indicates that 85.2% of the variance in training scores can be explained jointly by these three variables. The study concludes that self-confidence, concentration, and goal setting are significantly and simultaneously associated with routine training scores. The development of psychological aspects such as self-confidence, the ability to focus, and structured training goals is a crucial part of athlete development, particularly for archers in the BPPLOP Archery Program of Central Java, in order to achieve optimal training outcomes.